Crystal structures and electronic properties in 3d transition metal doped SrRuO3. Issue 14 (22nd March 2019) - Qasim, Ilyas; Blanchard, Peter E. R.; Knight, Kevin S.; Ting, Jimmy; Kennedy, Brendan J.
Abstract : The synthesis of polycrystalline samples of B-site doped SrRu1− x M x O3 with x ≤ 0.2 by solid state methods is described for a number of dopants (M = Mg, Mn, Fe, Co, Ni, Cu, or Zn) and the structures of these established using Synchrotron X-ray powder diffraction, and for SrRu0.8 Cu0.2 O3 high resolution neutron diffraction. Abstract : The synthesis of polycrystalline samples of B-site doped SrRu1− x M x O3 with x ≤ 0.2 by solid state methods is described for a number of dopants (M = Mg, Mn, Fe, Co, Ni, Cu, or Zn) and the structures of these established using Synchrotron X-ray powder diffraction, and for SrRu0.8 Cu0.2 O3 high resolution neutron diffraction. With the exception of M = Cu, samples with x = 0.2 form an orthorhombic Pbnm type perovskite structure at room temperature and these exhibit a sequence of phase transitions upon heating associated with the gradual reduction in the cooperative tilting of the corner sharing octahedra. SrRu0.8 Cu0.2 O3 forms a unique monoclinic structure at low temperatures and this transforms to the cubic Pm 3̄ m structure via an I 4/ mcm intermediate upon heating. The magnetic and electronic properties of the samples have been studied. Doping results in a decrease in the Curie temperature and at x = 0.2 all the samples are insulators. This is a consequence of the partial oxidation of the Ru cation that narrows the Ru 4d bands coupled with the suppression of the itinerant nature of the Ru 4d electrons due to the random distribution of the dopant cations. Ru L3 -edge X-ray absorption spectroscopy of the Cu doped samples reveal a gradual increase in the average Ru oxidation sate upon doping. Electrical resistivity measurements show that doping increases the resistivity of the samples, and the temperature dependence of the resistivities are consistent with Arrhenius-type charge conduction.